2017
DOI: 10.1590/1983-21252017v30n128rc
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Models for Description of Cacao Fruit Growth With Assumption Violations

Abstract: -Cacao (Theobroma cacao L.) is an important fruit in the Brazilian economy, which is mainly cultivated in the southern State of Bahia. The optimal stage for harvesting is a major factor for fruit quality and the knowledge on its growth curves can help, especially in identifying the ideal maturation stage for harvesting. Nonlinear regression models have been widely used for description of growth curves. However, several studies in this subject do not consider the residual analysis, the existence of a possible d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
(27 reference statements)
8
38
1
4
Order By: Relevance
“…Similar findings were reported by PRADO et al, (2013); MUNIZ et al, (2017);MUIANGA et al, (2016) andSOUSA et al (2014). They recorded autocorrelated errors in the adjustment of the nonlinear regression models to the growth data of the green dwarf coconut, cacao and cashew fruits and coffee seed germination, respectively.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings were reported by PRADO et al, (2013); MUNIZ et al, (2017);MUIANGA et al, (2016) andSOUSA et al (2014). They recorded autocorrelated errors in the adjustment of the nonlinear regression models to the growth data of the green dwarf coconut, cacao and cashew fruits and coffee seed germination, respectively.…”
Section: Resultssupporting
confidence: 84%
“…Similar findings were reported by MUNIZ et al (2017), MUIANGA et al (2016) and CASSIANO & SÁFADI (2015) in their studies on growth, in which the residual dependence was modeled by autoregressive order AR P . In the current study, the logistic model offered the best results corroborating the findings of PRADO et al, (2013), who also reported a better fit by this model in their studies on the green dwarf cocus fruit diameter.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, the Gompertz and Logistic models are suitable for adjusting the productive traits of sunn hemp. In study on nonlinear models for description of cacao fruit growth with assumption violations, Muniz et al (2017), verified the importance of performing the residual analysis.…”
Section: Resultsmentioning
confidence: 90%
“…models in the description of cocoa fruit growth (Muniz, Nascimento, & Fernandes, 2017). Therefore, studies on growth models for productive character of sunn hemp are important to know the behavior of the culture, but no work has been found in the literature.…”
mentioning
confidence: 99%
“…In the fruit growth evaluation, several studies have used nonlinear regression models, which are more appropriate than linear ones, since they summarize data information in a few parameters with practical interpretation (BALAGUERA-LÓPEZ et al, 2012;MARO et al, 2012;PRADO et al, 2013a;FERNANDES et al, 2014). Nonlinear models have been used in studies in crops with satisfactory results, allowing estimations of fruit growth parameters with biological interpretation with pygmy date palm (TERRA et al, 2010), green dwarf coconut (PRADO et al, 2013b), cashew (MUIANGA et al, 2016 and cacao fruit (MUNIZ et al, 2017). For coffee crop, models were used in the description of the seed germination curve (SOUSA et al, 2014), in a plant height growth study and canopy diameter (WYZYKOWSKI et al al., 2015).…”
Section: Introductionmentioning
confidence: 99%